Peran Lingkungan Belajar dalam Mendorong Partisipasi Aktif Siswa Sekolah Dasar - Abd. Rahman Saleh (Jurnal Kajian Pendidikan dan Cakrawala Pembelajaran, 2025)
A conducive learning environment plays a central role in shaping the behavior and active participation of elementary school students. Active student participation includes their participation in class discussions, asking questions, answering questions, expressing opinions, and being involved in group activities. This literature study aims to examine how various aspects of the learning environment, both physical, social, and psychological, can affect the level of student participation. The method used is a literature study by reviewing 20 national and international journal articles published in 2018–2024. The results of the study show that five aspects of the learning environment have a significant influence on student activity, namely: classroom arrangement that supports interaction, a positive emotional climate, the role of teachers as facilitators, the use of innovative learning media, and the application of the principle of inclusivity. An environment that supports a sense of safety, comfort, and respect for diversity has been shown to encourage students to be more confident and active in the learning process. This article recommends that educators and schools create a learning environment that does not only focus on physical facilities, but also on a humanistic pedagogical and social approach. Thus, a learning space is created that is fun and empowers the full potential of students.